Promoting mental health with adolescents in brazilian schools: A scoping review protocol (Research, Society and Development, 2026)
This study aims to present the protocol of a scoping review guided by the question: “What does the literature report on mental health promotion with adolescents in Brazilian schools?”. The review will be conducted based on the Joanna Briggs Institute (JBI) methodology and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). It will include articles published between 2015 and 2025. Guided by the PCC framework, the review will consider, as Population, studies addressing interventions aimed at promoting adolescents’ mental health, according to the age range defined by the World Health Organization and adopted by the Brazilian Ministry of Health; as Concept, interventions, actions, projects, or programs focused on mental health promotion in schools providing secondary, middle and/or high school education; and as Context, the Brazilian setting, with no language restrictions. After a pilot study, the initial search will be conducted by three researchers in national (SciELO), Latin American (LILACS, CINAHL), and international databases (PubMed, Web of Science, and Scopus). Study inclusion and exclusion will be based on the analysis of titles, keywords, and abstracts. For data extraction from full-text articles, a data extraction tool developed in accordance with JBI guidelines will be used. Data synthesis and the final report will follow PRISMA-ScR recommendations. This scoping review is expected to contribute to mapping the scientific literature on mental health promotion among adolescents in the Brazilian school context, as well as to identifying gaps that may support the development of new practices and future research.